TEACHING ENGLISH VOCABULARY USING TPR (TOTAL PHYISICAL RESPONSE) METHOD AT THE FIFTH GRADE STUDENTS OF SDN CINERANG CIANJUR IN ACADEMIC YEAR OF 2017/2018 - Eka Eka; Julian Erischa Setiawan (IKIP Siliwangi, 2018)
The objective this research entitled “Teaching English Vocabulary Using TPR (Total Physical Response) Method at the Fifth Grade Students of SDN Cinerang Cianjur” was to find out whether or not teaching vocabulary using TPR was effective to improve the students’ vocabulary mastery. In this research, the writer used pre experimental design one group pretest and posttest design and quantitative research method. The instrument of this research was multiple choices reading test. The data of this research were collected by giving multiple choices reading test to the student sample. The data collected data used t-test formula. The result of analysis data showed that: mean score of pretest was 58,29, means score of posttest was 68,90, and the tobs was 9,07. The t critical value with d.f = n-1 (41-1=40) and significance level at 0.05 was 1.68. From the data analysis above, the alternative hypothesis of the research was accepted, because tobs was higher than t critical value (9,07 > 1,68). Using TPR Method in vocabulary was effective and can increase students vocabulary mastery. Keywords: Vocabulary, Physical Response, Teaching